PERKAWINAN DI BAWAH TANGAN PERSPEKTIF UU 1/1974 DAN VICTIMOLOGI - Khuluqi, Luthfah (Irtifaq, 2016)
As a sacred bond, marriage contains the value of ritual doctrine and is related to cultural social problems. Marital status gives an explanation of the consequences of legal obligations and responsibilities for husband and wife. To demonstrate the emergence of legally-enforceable legal consequences, the state makes a rule that marriage should be recorded by the Marriage Officer through the KUA. Unregistered marriage from law is considered never present. From Victimology, the legal act of marriage will bring harmful effects and cause casualties. Husbands and wives, parents may each be victims of marriages that are not registered under applicable laws. Circumstances can not get legal protection can occur when marriage bonds remain, especially when the marriage bond breaks up.Keyword : marital status, victimology, legal protection